Prevalence of depressive symptoms and its associated factors among the aging population in Gamo zone, Southern Ethiopia: a community-based cross-sectional study - Oumer, Bilcha; Abera, Rahel; Beshah, Asrat; Tesfaye, Selamnesh; Niguse, Tilhun; Mohammed, Bedria; Yimer, Awol Arega; Sidamo, Negussie Boti (Frontiers in Psychiatry, 2024)
Abstract Background: Depression in the elderly is becoming a major public health problem worldwide. It is a major public health problem associated with increased morbidity, mortality, and healthcare costs in low- and middle-income countries, including Ethiopia. However, especially in developing countries, they usually go undetected and untreated. There is little evidence of depressive symptoms among older people in Ethiopia. Therefore, this study aims to determine the prevalence of depressive symptoms and associated factors among the elderly population in the Gamo zone of southern Ethiopia. Methods: A community-based cross-sectional study was conducted among 840 randomly selected elderly individuals. A multi-stage sampling technique was employed to recruit participants. Depressive symptoms were assessed using the 15-item Geriatric Depression Scale (GDS) screening tool. Data collection was performed through face-to-face interviews. Descriptive statistics were initially computed. Subsequently, logistic regression analysis was conducted to identify independent factors associated with the outcome variable. Result: The finding of the study showed that the prevalence of depressive symptoms among older people living in the Gamo zone was 424(50.5%) (95% CI=47.1-53.9). Age 70–74 years [AOR=2.8, 95% CI 1.6-4.8], 75 years and above [AOR=5.1, 95% CI 3.0-8.6], age 65–69 years [AOR=2.4, 95% CI 1.6-3.7]; being widowed [AOR=2.7, 95% CI 1.7-4.4], ever chewing khat [AOR=5.9, 95% CI 1.2-29.5], being poor economic status [AOR=9.4, 95% CI 3.6-24.5], being average economic status [AOR=5.4, 95% CI 2.2-13.4], having 1–2 stressful life events [AOR=5.1, 95% CI 3.4-7.9], having 3 and above stressful life events[AOR=11.0, 95% CI 6.6,18.4], living alone[AOR=2.7, 95% CI 1.4-4.9] and those who lived with children [AOR=3.2, 95% CI 1.7-5.9] were significantly associated with depression. Conclusion: Half of the study participants exhibited depressive symptoms. Urgent interventions are essential to enhance psychological well-being and mitigate the impact of various modifiable risk factors associated with depression in elderly individuals. Efforts should focus on increasing social support, especially for those who have experienced stressful life events, live alone, or have low economic status. Healthcare providers should implement routine screening for depressive symptoms and offer supportive counseling. Policymakers and stakeholders need to prioritize improving access to mental health services.